Frito crisps: snacks for Norte de Santander (Ingeniería, Sostenibilidad y Sociedad, 2020)
The project proposes the creation of a snack production plant, with the aim of offering a service with the best value for money, so that it can gain greater acceptance among consumers and, in turn, become their favorite brand. The company will offer quality products at an affordable price for as many people as possible, so that this type of food product can be enjoyed at any time without any inconvenience.The project will be located in the city of Cúcuta, Norte de Santander, and the aim is to be present in as many of the department's 40 municipalities as possible, becoming a leading brand at the regional level and subsequently expanding.
Keywords: Snacks for Norte de Santander; processing; industrial plants; value added